1979
DOI: 10.1128/iai.26.2.520-527.1979
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-sensitive interaction of Escherichia coli with human peripheral leukocytes in vitro

Abstract: The ability of Escherichia coli which possess or lack mannose-sensitive adherence factors (adhesins) to associate with human peripheral leukocytes in vitro in the absence of serum was studied. E. coli 19+, which have mannose-sensitive adhesins, were derived from E. coli strain 19 by culturing in static Trypticase soy broth at 37 degrees C. E. coli 19-, which lack mannose-sensitive adhesins, were derived from E. coli 19 by culturing in agitated Trypticase soy broth at 30 degrees C. E. coli 19+ attached to leuko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 28 publications
2
51
0
Order By: Relevance
“…The monosaccharide D-galactose, which is a significant component of erythrocyte glycoproteins (Emerson & Kornfeid 1976) and F. nucleatum lipopolysaccharide (Fredriksen & Hofstad 1978, Kristoffersen & Hofstad 1970, caused significant inhibition of PMN chemiluminescence in response to F. nucleatum. Inhibition of PMN chemiluminescence required a moderately large concentration of Dgalactose (100 mM) compared to alpha-methyl-D-mannoside inhibition of PMN chemiluminescence in response to Fscherichia fo/j (Mangan & Snyder 1979). The inhibition of chemiluminescenee by D-gaiactose appeared to be a reversible, non-covalent interaction since centrifugation washes were able to restore a normal PMN response to F. nucleatum.…”
Section: Phagocytosis Of Bacteria and Other Particles Bymentioning
confidence: 92%
“…The monosaccharide D-galactose, which is a significant component of erythrocyte glycoproteins (Emerson & Kornfeid 1976) and F. nucleatum lipopolysaccharide (Fredriksen & Hofstad 1978, Kristoffersen & Hofstad 1970, caused significant inhibition of PMN chemiluminescence in response to F. nucleatum. Inhibition of PMN chemiluminescence required a moderately large concentration of Dgalactose (100 mM) compared to alpha-methyl-D-mannoside inhibition of PMN chemiluminescence in response to Fscherichia fo/j (Mangan & Snyder 1979). The inhibition of chemiluminescenee by D-gaiactose appeared to be a reversible, non-covalent interaction since centrifugation washes were able to restore a normal PMN response to F. nucleatum.…”
Section: Phagocytosis Of Bacteria and Other Particles Bymentioning
confidence: 92%
“…No fimbriae, pili, or flagella were seen on either strain when negatively stained and examined by transmission electron microscopy (not shown). In comparison, pili on Escherichia coti were readily visible using this procedure (11).…”
Section: Adherence Of F Nucleatum To Lymphocytes 81mentioning
confidence: 97%
“…These growth conditions yield smooth E. coli that possess mannose-sensitive adhesions . Mannose binding capacity, shown by other investigators to be related to the presence oftype I pili, was demonstrated by the capacity of this E. coli isolate to agglutinate guinea pig erythrocytes (24,25) and saccharomyces cerevisiae yeast cells (10) as determined by the methods of Eden and Hansson (24) and Bar Shavit et al (10), respectively . This agglutination was specifically inhibited by 0.20 M a-methylmannoside .…”
Section: Methodsmentioning
confidence: 83%